Sociolinguistic Variations in Arabic Dialects: A Comparative Study of Classical and Colloquial Arabic / الاختلافات الاجتماعية اللغوية في اللهجات العربية: دراسة مقارنة بين العربية الفصحى والعامية - Ahmed Souri; Ria González (IJAS: International Journal of Arabic Studies, 2025)
This study investigates the sociolinguistic differences between Modern Standard Arabic (MSA) and Arabic dialects through a comparative approach. The research aims to analyze how social factors such as age, education, and cultural background influence language variation and usage in different contexts. Using qualitative and quantitative methods, data were collected through interviews, observations, and documentation from diverse Arabic-speaking communities. The results reveal significant linguistic variations in phonology, morphology, syntax, and pragmatics, demonstrating the coexistence and interaction of MSA with local dialects. The findings highlight that while MSA maintains its prestige and official role in education, media, and formal communication, dialects dominate daily interactions and reflect regional identities. This study contributes to the understanding of Arabic sociolinguistics and provides insights into language policy, education, and cross-cultural communication.